The Effect of Work Motivation and Work Discipline on Employee Performance - Rozi, Fahrur; Widiyanti, Marlina; Yusuf, Muhammad; Ichsan Hadjri, Muhammad (Jurnal Multidisiplin Indonesia, 2024)
This study was conducted with the aim of determining the influence of work motivation and work discipline on employee performance (case study on PT Kilang Pertamina Internasional RU III Plaju). The population in this study is all employees at PT Kilang Pertamina Internasional RU III Plaju as many as 868 employees in 2024. The sample used in this study was 148 respondents using the proportional random sampling method in determining the sample. The results of multiple linear regression analysis show that work motivation and work discipline have a positive and significant effect on employee performance. Work motivation is expected for PT Kilang Pertamina Internasional RU III Plaju to form work team members that need to be adjusted to the appropriate level of education, appropriate work experience, and additional skills possessed by employees. Work discipline, the application of sanctions for employees who have been warned not to repeat their mistakes. In addition, the use of protective equipment at work needs to be maintained to avoid work accidents.